Antimicrobial Resistance in Bacteria Isolated From Canine Urine Samples Submitted to a Veterinary Diagnostic Laboratory, Illinois, United States - Yudhanto, Setyo; Hung, Chien-Che; Maddox, Carol W.; Varga, Csaba (Frontiers in Veterinary Science, 2022)
The emergence of antimicrobial resistance (AMR) in dogs constitutes a threat to animal and human health. There is a lack of studies in Illinois that evaluated the prevalence of AMR among urinary bacterial pathogens. In the study, we included 803 isolates (299 Gram-positive and 504 Gram-negative) that were isolated from 2,583 canine urine samples submitted to the Veterinary Diagnostic Laboratory, the University of Illinois between 2019 and 2020 from dogs suspected of urinary tract infections (UTI). The most common Gram-positive isolates included Staphylococcus pseudintermedius (17.93%), Enterococcus faecalis (9.46%), Streptococcus canis (6.10%), and Enterococcus faecium (3.74%), while Gram-negative isolates included Escherichia coli (45.58%), Proteus mirabilis (11.08%), Klebsiella pneumoniae (3.11%), and Pseudomonas aeruginosa (2.99%). Among the Gram-positive isolates, Staphylococcus pseudintermedius isolates showed a very high prevalence of resistance to penicillin (56.94%), a high prevalence of resistance to trimethoprim-sulfamethoxazole (31.94%), enrofloxacin (29.17%), and oxacillin (27.08%). Among Gram-negative bacteria, Escherichia coli isolates showed a high prevalence of resistance to ampicillin (31.42%). Considering the high prevalence of resistance to antimicrobials commonly used to treat UTI in dogs, urine samples should be collected for bacterial culture and susceptibility testing before treatment initiation to prevent treatment failures and the development of multidrug resistance. Given the possibility of zoonotic transmission of antimicrobial-resistant bacteria, veterinarians when treating UTI cases, should inform dog owners of the potential transmission risk.